Testing a Subset of the Overidentifying Restrictions - Kadane, Joseph B. (Econometrica, 1974)
A family of tests of significance is developed for coefficients in a single equation of a simultaneous system., Different members of this family are distinguished by the k-class estimator on which they are based, and on the alternative hypothesis against which they test. The size of the test is found when the disturbances are small, and the test is shown to be consistent if plim k = 1 or k = Î», the limited information maximum likelihood value.